Penerapan konseling kelompok untuk mencegah perilaku konformitas negatif siswa SMK Negeri 5 Semarang - Suhendri, Suhendri (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
Conformity is basically very important in the life of every individual. Conformity among teenagers who are teenagers is very important, because they will be racing to find their identity. However, when students do not have self control in association it will cause negative conformity. Also vice versa if in association students are able to control himself, it will give birth to positive coformity. Where in adolescence is always dominant sense or emotional aspects. Teen age emotional aspects still include emotional unstable or uncontrolled. Thus allowing uncontrolled behaviors to occur. The impact of negative conformity of students, such as brawl, makes the relationship between schools to be less harmonious and very disturbing the public and disrupt traffic on the highway when students do brawl. Even based on the revelation of the BK Teacher, stated that some students were arrested by the police when they did brawl. The final goal of this study is to prevent the occurrence of negative conformity behavior of students In accordance with research objectives, then this research method using quantitative research methods. Design one gruop pre test and post test design. In this subject design is subjected to two measurements, namely by using a scala psychological-related negative conformity behavior of students. Based on the result of classification of pree test and post test mentioned above there is difference of procession that is 36,63%. So it can be concluded that in this study there is a positive change in students who initially have very negative negative conformity behavior, but after given the guidance service group, the behavior of student conformity becomes low.